Weekly chemotherapy with radiation versus high‐dose cisplatin with radiation as organ preservation for patients with HPV‐positive and HPV‐negative locally advanced squamous cell carcinoma of the oropharynx. Issue 5 (2nd July 2013) - Dobrosotskaya, Irina Y.; Bellile, Emily; Spector, Matthew E.; Kumar, Bhavna; Feng, Felix; Eisbruch, Avraham; Wolf, Gregory T.; Prince, Mark E. P.; Moyer, Jeffrey S.; Teknos, Theodoros; Chepeha, Douglas B.; Walline, Heather M.; et al.
<x xml:space="preserve">Abstract</x> Background Optimal treatment for locally advanced squamous cell carcinoma of the oropharynx (SCCOP) is not well defined. Here we retrospectively compare survival and toxicities from 2 different organ preservation protocols. Methods The matched dataset consisted of 35 patients from each trial matched for age, stage, smoking, and tumor human papillomavirus (HPV) status. Patients in the University of Michigan Cancer Center (UMCC) trial 9921 were treated with induction chemotherapy (IC) followed by high‐dose cisplatin and radiation in responders or surgery in nonresponders. Patients in the UMCC trial 0221 were treated with weekly carboplatin and paclitaxel and radiation. Results Survival was comparable for both studies and did not differ significantly across each trial after stratifying by HPV status. Grade 3 and 4 toxicities were more frequent in UMCC 9921. At 6 months posttreatment, gastrostomy tube (G‐tube) dependence was not statistically different. Conclusion These data suggest that survival outcomes in patients with locally advanced SCCOP are not compromised with weekly chemotherapy and radiation therapy, and such treatment is generally more tolerable. © 2013 Wiley Periodicals, Inc. Head Neck36: 617–623, 2014